Intersectionality and Policy-Making: Structural Barriers to Entrepreneurship for Black African Females in Finland (Politeja, 2019)
The paper summarizes the literature on the role of intersectionality in researchand policy-making. Twisting the categories of race, class, gender and nationality, the current study explores structural obstacles faced by black African businesswomen in Finland. The findings suggest that the Finnish opportunity structureis both legally and socially unprepared for accepting African female entrepreneurs as equal economic actors. Based on the structural barriers identified, the paper presents several policy recommendations including fair involvement of migrants in the process of policymaking, better coordination of policies for newcomers, and creation of migrant entrepreneurship hubs. In addition, the study assumes that intersectional identities can act as both vulnerable and powerful depending on a context of interaction, which may provide grounds for redefining the very focus of intersectionality. Finally, the paper determines prospective research directions.